GREEN MARKETING, ENVIRONMENTAL AWARENESS, AND PURCHASE INTENTION OF ECO BAGS: A STUDY OF PRIVATE VOCATIONAL SCHOOL TEACHERS IN BEKASI REGENCY - Sarmin; Suryana; Siva Marsya Oktaviany (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of Green Marketing and Environmental Awareness on consumers' intention to purchase environmentally friendly bags at minimarkets, both separately and simultaneously. This study uses a quantitative and associative approach. The study involved private vocational school teachers in Bekasi Regency, with 341 respondents selected at random. After data collection through questionnaires, instrument testing, classical assumptions, and hypothesis testing were conducted using multiple linear regression with SPSS version 26.0. The results indicate that the desire to purchase ECO BAGs is partially influenced by green advertising and environmental awareness. Additionally, both independent variables significantly influence the dependent variable. According to the coefficient of determination (R²) value of 0.747, green advertising and environmental awareness can explain 74.7% of the interest in purchasing variable. Other variables outside the research model influence 25.3%. Therefore, companies should use Green Marketing strategies and increase environmental awareness in their communications to encourage customers to purchase environmentally friendly products such as ECO BAGs.